Ketercapaian Empat Keterampilan Abad 21 Pada Pengembangan Modul Social Media Marketing - Putera, apriyanto Hadi; Harti, Harti; Sakti, Norida Candra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the achievement of 4C’s of 21st century skills, namely critical thinking; creative, communicative, and collaborative on the use of modules developed using the ADDIE method. In the developed module, there are marketing topics using social media, assignments and practice questions that contain 4C skills. Module development and testing begins with preliminary observations about the need for teaching materials for students who are taking industrial work practice (internship), then designing modules based on input, followed by validating the material and media in the module, testing on students and ending with a questionnaire sheet and student self-assessment sheets in using modules during internship. From all these steps, the module is declared very suitable for use. Keywords: module, four skills, 4C, internship